Injury Investigations in anti-Dumping and the Super-Additivity Effect : A Theoretical Explanation - Gupta, Poonam (IMF Working Papers; Working Paper ;, 2001)
Empirical evidence shows that injury investigations in anti-dumping cases conducted by the United States International Trade Commission, the probability of a positive finding is higher when the number of defendant firms is larger, holding constant their total market share. In this paper we offer a theoretical explanation of this finding. We show that the presence of many exporters exacerbates the free-rider problem, which leads every firm to invest less on defense. Thus for the same market share, injury finding is more likely to be positive for many small sellers than a few large sellers.